Writing Through Scaffolding Technique Using Online Platform in Senior High School - Putra, I Made Deby Adi Gunawan (Jurnal Pendidikan Bahasa Inggris undiksha, 2023)
Writing is an important skill and also an effective language skill, which is why students need to pay special attention to their writing skills. This study was aimed to analyze how to implement teachers in teaching through scaffolding technique using online learning platform in senior high school. The method used was documentation and in-depth interviews were conducted to collect data and answer a research question.  In other words, all data in this study were obtained from the main source because it came directly from the main source, namely the student. The research findings show that in the application of teaching teachers using scaffolding technique using online platform in the senior high school students had difficulty converting sentences into simple tenses, students had difficulty developing main ideas to make supporting sentences and students had difficulty only making part of events and lacking in more in-depth character recognition. Suggestions for teachers should knew how to encourage more students to keep them interested in learning about writing. So that it can make it easier for students and interested in learning to write in class.